2018
DOI: 10.1038/s41598-018-32019-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of Atlantic salmon gills reveals mucin 5 and interleukin 4/13 as key molecules during amoebic gill disease

Abstract: Amoebic gill disease (AGD) is one of the main diseases affecting Atlantic salmon (Salmo salar L.) mariculture. Hallmarks of AGD are hyperplasia of the lamellar epithelium and increased production of gill mucus. This study investigated the expression of genes involved in mucus secretion, cell cycle regulation, immunity and oxidative stress in gills using a targeted 21-gene PCR array. Gill samples were obtained from experimental and natural Neoparamoeba perurans infections, and sampling points included progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 94 publications
5
43
2
Order By: Relevance
“…Another highly expressed transcript is involved in T-cell function, T-cell specific surface glycoprotein CD28 ( CD28 ; logFC = 1.60). CD28 promotes T-cell survival and proliferation, and enhances the production of multiple cytokines including IL4 (Blotta et al 1996) IL4 has been found to be up-regulated in response to AGD (Marcos-López et al 2018), and this gene induces differentiation of naïve helper T cells to Th2 cells. The Th2 pathway was found to be up-regulated in late stages of AGD (Benedicenti et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another highly expressed transcript is involved in T-cell function, T-cell specific surface glycoprotein CD28 ( CD28 ; logFC = 1.60). CD28 promotes T-cell survival and proliferation, and enhances the production of multiple cytokines including IL4 (Blotta et al 1996) IL4 has been found to be up-regulated in response to AGD (Marcos-López et al 2018), and this gene induces differentiation of naïve helper T cells to Th2 cells. The Th2 pathway was found to be up-regulated in late stages of AGD (Benedicenti et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This gene inhibits apoptosis by suppressing the activity of caspase-8 (You et al 2001). The down-regulation of pro-apoptotic genes has been connected to AGD severity (Marcos-López et al 2018). The lack of a clear picture in head kidney might reflect the relative importance of the local and systemic immune responses in response to AGD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, study of immunological responses within the gill has highlighted the potential role of secreted IgT responses, in part delivered through mucus, as well as gene expression reflecting production of other defensins carried in mucus and acting against gill pathogens (Brinchmann, 2016;Xu et al, 2016) and their correlated pathology (Benhamed, Guardiola, Mars, & Esteban, 2014;Hishida, Ishimatsu, & Oda, 1997). Additionally, mucins have been investigated as reliable markers of prognostic and diagnostic value of fish intestinal health (Estensoro, Calduch-giner, Pe, Kaushik, & Sitja, 2013;Marcos-López et al, 2018). Is therefore a need to maintain the mucous coat in order to identify the pathogens embedded in it and potentially study their relationship with the mucus secretions.…”
Section: Discussionmentioning
confidence: 99%